Entrepreneurial orientation, knowledge management, dynamic capabilities towards e-commerce adoption of SMEs in Indonesia. Issue 2 (26th January 2021) - Nasution, Muhammad Dharma Tuah Putra; Rafiki, Ahmad; Lubis, Adelina; Rossanty, Yossie
Abstract : Purpose: The purpose of this study is to examine the dimensions of entrepreneurial orientation (EO), knowledge management process (KMP) and dynamic capability (DC) toward the adoption of electronic commerce (e-commerce) of small and medium enterprises (SMEs) in North Sumatera. Design/methodology/approach: This study used a quantitative methodology using Smart PLS of structural equation model. A survey is done by distributing the questionnaires to the respondents (owner-managers) of SMEs across sectors. Using a convenient sampling technique, 131 respondents were selected. Using a cross-sectional survey design, 11 hypotheses were tested. Findings: It is found that both innovativeness and proactiveness of EO have a significant relationship with e-commerce adoption (EA), while the risk-taking of EO is found as insignificant. Both risk-taking and proactiveness of EO are significantly related to KMP, but innovation of EO is found to be insignificant. Moreover, KMP significantly mediates the relationship between risk-taking and proactiveness of EO and EA, while KMP insignificantly mediates the relationship between innovativeness of EO and EA. Finally, it is found that DC has a significant relationship in EA. Originality/value: By using the resource based-theory, the study on the decision of EA by SMEs is conducted which focuses on a number of internal and external factors influencing the adoption decision. This differs from other studies using theories of the technological, organizational and environmental, theory of acceptance and use of technology, theory of planned behavior, theory of reasoned action and others which emphasized on the implementation and usage of EA.